The efficacy of sarang semut extract (Myrmecodia pendens Merr & Perry) in inhibiting Porphyromonas gingivalis biofilm formation - Zulfan M. Alibasyah; Ambrosius Purba; Budi Setiabudiawan; Hendra Dian Adhita; Dikdik Kurnia; Mieke H. Satari (Dental Journal (Majalah Kedokteran Gigi), 2017)
Background: Porphyromonas gingivalis (P. gingivalis) is a pathogenic bacteria present in the oral cavity involved in the pathogenesis of chronic periodontitis and biofilm. This mass of microorganisms represents one of the virulent factors of P. gingivalis which plays an important role as an attachment initiator in host cells. Sarang semut is a natural material possessing the ability to inhibit the growth of P. gingivalis. Purpose: This study aims to analyze the effect of sarang semut extract on the formation of P. gingivalis biofilm. Methods: The study used methanol sarang semut extract and P. gingivalis ATCC 33277 and phosphomycin as a positive control. Treatment was initiated by means of culturing. Biofilm test and P. gingivalis biofilm formation observation were subsequently performed by means of a light microscope at a magnification of 400x. Results: The formation of P. gingivalis biofilms tended to increase at 3, 6, and 9 hours. Results of the violet crystal test showed that concentrations of 100% and 75% of the sarang semut extract successfully inhibited the formation of P. gingivalis biofilm according to the incubation time. Meanwhile, the sarang semut extracts at concentrations of 50%, 25%, 12.5%, and 6.125% resulted in weak inhibition of the formation of P. gingivalis biofilm. The biofilm mass profile observed by a microscope tended to decrease as an indicator of the effects of the sarang semut extract. Conclusion: Sarang semut extract can inhibit the formation of P. gingivalis biofilm, especially at concentrations of 100% and 75%. Nevertheless, phosphomycin has stronger antibiofilm of P. gingivalis effects than those of the sarang semut extract at all of the concentrations listed above.